SILAC‐based quantitative proteomic analysis reveals widespread molecular alterations in human skin keratinocytes upon chronic arsenic exposure. Issue 6 (21st December 2016) - Mir, Sartaj Ahmad; Pinto, Sneha M.; Paul, Somnath; Raja, Remya; Nanjappa, Vishalakshi; Syed, Nazia; Advani, Jayshree; Renuse, Santosh; Sahasrabuddhe, Nandini A.; Prasad, T. S. Keshava; Giri, Ashok K.; Gowda, Harsha; et al.
Abstract : Chronic exposure to arsenic is associated with dermatological and nondermatological disorders. Consumption of arsenic‐contaminated drinking water results in accumulation of arsenic in liver, spleen, kidneys, lungs, and gastrointestinal tract. Although arsenic is cleared from these sites, a substantial amount of residual arsenic is left in keratin‐rich tissues including skin. Epidemiological studies suggest the association of skin cancer upon arsenic exposure, however, the mechanism of arsenic‐induced carcinogenesis is not completely understood. We developed a cell line based model to understand the molecular mechanisms involved in arsenic‐mediated toxicity and carcinogenicity. Human skin keratinocyte cell line, HaCaT, was chronically exposed to 100 nM sodium arsenite over a period of 6 months. We observed an increase in basal ROS levels in arsenic‐exposed cells. SILAC‐based quantitative proteomics approach resulted in identification of 2111 proteins of which 42 proteins were found to be overexpressed and 54 downregulated (twofold) upon chronic arsenic exposure. Our analysis revealed arsenic‐induced overexpression of aldo‐keto reductase family 1 member C2 (AKR1C2), aldo‐keto reductase family 1 member C3 (AKR1C3), glutamate‐cysteine ligase catalytic subunit (GCLC), and NAD(P)H dehydrogenase [quinone] 1 (NQO1) among others. We observed downregulation of several members of the plakin family including periplakin (PPL), envoplakin (EVPL), and involucrin (IVL) that are essential for terminal differentiation of keratinocytes. MRM and Western blot analysis confirmed differential expression of several candidate proteins. Our study provides insights into molecular alterations upon chronic arsenic exposure on skin.